Computing Support in Statistical Evaluation of Mathematics Teaching Effectiveness: Development of Students’ Constructive Thinking - Mihajlov Carević, Miroslava; Petrović, Milena; Denić, Nebojša; Mitrović, Aleksandra (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
One of the main tasks in teaching mathematics is to develop students’ constructive thinking. In order to effectively accomplish this task, it is necessary to make a good selection of instructional materials and teaching aids. In order to make good selection and improve the teaching of mathematics, it is, also, necessary to include a statistical analysis of the certain factors’ impact that affect mathematics curriculum. For the purpose of this research, we used the software computational approach ANFIS (adaptive neuro fuzzy inference system) to determine the qualitative impact of several factors on improving students’ ability to create constructive thinking.